The Power of Music and Movement in Educational Videos on Stunting - Andika, Windi Dwi; Akbari; Dwi Cahaya Nurani; Yuni Dwi Suryani; Sri Sumarni; Yin Yin Septiani; Ruri Tria Astika; Putri Salsabila; Fita Rizkika Fizmayani; Risca Cahya (Universitas Pendidikan Ganesha, 2025)
Stunting is a serious issue that affects early childhood development and demands educators' attention in providing appropriate preventive education. Ironically, the limited availability of effective educational media for stunting prevention hinders the learning process. This study aims to develop and evaluate the feasibility of an educational video based on movement and song activities as a preventive effort against stunting in early childhood. This research employed a research and development (R&D) design involving 28 children as subjects. Data were collected through observation and structured interviews, and analyzed using qualitative descriptive methods. The findings indicate that the developed educational video effectively conveys health messages in an engaging and child-friendly manner. The content covers healthy living habits, nutritious food consumption, and regular sleep patterns, all demonstrated through songs and movements. Both children and teachers showed high enthusiasm after using the media consistently for two weeks. The study concludes that movement and song based educational videos are appropriate as a medium for stunting prevention education in early childhood. The implications of this study highlight the importance of developing creative, enjoyable, and behavior-oriented learning media to foster healthy habits from an early age. Further development is recommended to ensure the sustainability and broader applicability of this media in various educational contexts.